peran mediasi paradigma lingkungan baru (new environmental paradigm/NEP) dalam faktor-faktor predisposisi yang memengaruhi perilaku bijak terhadap lingkungan - Agus Priadi; Erian Fatria; Eka Apriyanti (Biosfer: Jurnal Pendidikan Biologi, 2026)
Modern society's environmental uncitizenship behavior is reflected in the accelerating impacts of climate change, biodiversity loss, natural disasters, environmental health problems, and resource depletion. This study aims to examine the influence of Environmental Leadership (EL), Ecological Intelligence (EI), and Personality Traits (PT) as predisposing factors of Environmental Citizenship Behavior (CB) among 40 university students selected through purposive sampling, with the New Environmental Paradigm (NEP) serving as a mediating variable. This research employed a quantitative approach using a causal study design. Data were collected through a calibrated questionnaire as the research instrument, and the data were analyzed using path analysis. The findings reveal that students' Environmental Citizenship Behavior (CB) in Bukittinggi is directly and significantly affected by Environmental Leadership (EL) (ρ = 0.520, p < 0.01) and the New Environmental Paradigm (NEP) (ρ = 0.388, p < 0.05). Furthermore, Environmental Leadership (EL) also exerts a significant direct effect on shaping students' environmental worldview, represented by the New Environmental Paradigm (NEP) (ρ = 0.257). In contrast, Personality Traits (PT) (ρ = 0.027) and Ecological Intelligence (EI) (ρ = 0.007) exhibit direct but statistically insignificant effects on both Environmental Citizenship Behavior (CB) and the New Environmental Paradigm (NEP). A highly significant direct effect on the development of students' New Environmental Paradigm (NEP) (ρ = 0.575). Sustainability interventions should not rely solely on students' inherent personality characteristics or theoretical ecological intelligence. A practical recommendation is to design and implement a Green Transformational Leadership program across the university through environmentally oriented leadership training for lecturers and student organization leaders.